Meteora Advertising Sdn Bhd / Mohd Afhizan Mohd Som ... [et al.] - Mohd Som, Mohd Afhizan; Othman, Nooriwan; Yahya, Adilaa; Jailani, Junaidah (Faculty of Civil Engineering, 2003)
Meteora Advertising Sdn Bhd is establishing consistent to our government exclamation towards 2020 which encourage our local peoples to plunge in business industry. So that we take this opportunity to run a business which can gives advantageous to all parties. Meteora Advertising Sdn Bhd is a company who run a service business which produce advertising product involving acrylic, sticker and steel. Our company offered a different of choice in producing a signage, signboard, stickers, banner and bunting. Our business done by customer's bookings first and then we will produce the product. In our company, the business can be done by a phone call and walk-in order. We will negotiate with clients and discuss for what they want and then after the negotiation agreed, then the business is deal. Instead of do not want to lose the deal, we will ask for an advance payment for a security. The rate of advanced payment is around 5%- 50%. This money is used for back up for our cost in case of if the clients cancel their order. Extra payment also granted if modifications wanted by the customers. It depends on the how its cost and recalculation on the total of payment will do.